2012
DOI: 10.1007/s10337-011-2173-5
|View full text |Cite
|
Sign up to set email alerts
|

Inside-Needle Extraction Method Based on Molecularly Imprinted Polymer for Solid-Phase Dynamic Extraction and Preconcentration of Triazine Herbicides Followed by GC–FID Determination

Abstract: An inside-needle extraction method was developed through thermal polymerization of atrazinemolecularly imprinted polymer (MIP) on the internal surface of a stainless steel hollow needle, which was oxidized and silylated. The fabricated coating (MIP layer) for the needle was durable and showed very good chemical and thermal stability. It could be mounted on a glass syringe and be directly coupled with gas chromatographic (GC) systems. The parameters being effective on the coating and extraction processes, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…However, the LODs achieved in proposed method are better than that obtained in SPME–GC–FD and solid‐phase dynamic extraction–GC–FD . It also can be seen from the Table that the spiked recoveries achieved in the present method are better than hollow fiber extraction–HPLC–UV and are comparable with other studies . The comparative results well indicate that the proposed PBM/MMF‐SPME procedure possesses some advantageous such as simple operation, cost‐effectiveness, and high sensitivity.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…However, the LODs achieved in proposed method are better than that obtained in SPME–GC–FD and solid‐phase dynamic extraction–GC–FD . It also can be seen from the Table that the spiked recoveries achieved in the present method are better than hollow fiber extraction–HPLC–UV and are comparable with other studies . The comparative results well indicate that the proposed PBM/MMF‐SPME procedure possesses some advantageous such as simple operation, cost‐effectiveness, and high sensitivity.…”
Section: Resultssupporting
confidence: 74%
“…For example, SPE-GC-MS [30], dispersive micro (Dμ)-SPE-UHPLC-MS [32], and IT-SPME-LC-MS-MS [35] show better sensitivity than our method. However, the LODs achieved in proposed method are better than that obtained in SPME-GC-FD [34] and solid-phase dynamic extraction-GC-FD [39]. It also can be seen from the Table 4 that the spiked recoveries achieved in the present method are better than hollow fiber extraction-HPLC-UV [40] and are comparable with other studies [11][12][13][14][28][29][30][31][32][33][34][35][36][37][38][39]41].…”
Section: Spe-hplc/uvsupporting
confidence: 81%
“…In fact, the use of SERS for prometryn in the literature has never gone below 10 -4 mol/L [24]. Prometryn detection with chromatography techniques has reached limits from 10 -6 to 10 -10 mol/L [31,32] while the differential pulse polarographic method led to detection of atrazine, prometryn, and simazine herbicides down to 8 9 10 -8 mol/L [7]. Oliveira-Brett et al [33] reported an electrochemical biosensor to investigate the interactions Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The tubes were treated by a method similar to reported previously [31]: In brief, they were cut into pieces each 6 cm in length and were immersed in a dilute commercial laundry detergent solution for 30 min at 70°C. Afterwards, they were washed and rinsed with distilled water and acetone, consecutively followed by an aqueous solution containing 50 g·L −1 sodium nitrite and 10 gL −1 sodium carbonate for 30 min at 60°C.…”
Section: Treatment Of Stainless Steel Tubesmentioning
confidence: 99%
“…We have previously reported some monolithic SPME fibers based on MIP which can be coupled with GC or GC/MS for selective extraction of different compounds from various samples [21,29,30]. In the previous work, we coated a selective sorbent layer (atrazine-MIP) on the inner surface of the oxidized and silylated stainless steel extraction needle through chemical bonding and used to SPDE of triazine herbicides from aqueous samples [31]. The aim of this study is to develop INAT method based on MIP using MAMP as template, and its application for SPDE of MAMP, AMP and MDMA from urine samples and analyses by GC-FID.…”
Section: Introductionmentioning
confidence: 99%